Lácteos: atributos valorizados na compra, perfil de ácidos graxos e efeitos do ácido linoléico conjugado no metabolismo lipídico - Fuke, Gitane (2012)
The relationships between nutrition and health have been studied throughout recent years as a result of the growing concern about the population s health. Consumers are increasingly more demanding about the quality of food consumed, inclusively worrying about attributes that go beyond the presence of nutrients and food security, but also concerning about health benefits. The following research aimed to understand which consumer perceptions about the role of animal fats in health and attributes are valued in buying dairy products, determining the levels of conjugated linoleic acid in milk produced in the state of Rio Grande do Sul as well as assessing the antiatherogenic potential of conjugated linoleic acid. In the first chapter of the thesis it was analyzed the behavior of consumers before the purchase of milk, where it is observed that 83% of respondents consume milk and crucial aspects for the consumer is the relationship price and taste. There is a good perspective on buying products with higher levels of conjugated linoleic acid and bringing benefits to consumer s health. Due to the wide and varied range of dairy products, consumer was induced to become more demanding about the quality of the product offered. In Chapter 2, it was determined the fatty acid profile in dairy (milk, cheese, and butter) produced in the state of Rio Grande do Sul and it was found that the composition was similar in both types of milk products produced in Rio Grande do Sul, including as to the presence of conjugated linoleic acid. CLA levels varied according to regions and seasons studied, which showed higher levels in the southern portion of the state and in the spring and winter. The CLA content in milk products produced in southern Brazil have higher values than those reported for dairy products from other countries, including those of temperate climate, which show higher values of this constituent. In chapter, it was assessed the effect of different lipid sources and antiatherogenic potential of conjugated linoleic acid in rabbits fed a diet containing butter, margarine, soybean oil, and synthetic CLA. The results, through hierarchical cluster analysis, showed similar variables in animals that consumed butter and soybean oil + CLA and another group with margarine and soy oil. HDL levels were higher in the treatment that received diet with conjugated linoleic acid and LDL was reduced. The reasons TC:HDL and LDL:HDL significantly increased in the group that consumed margarine. The inclusion of CLA, even at low levels, such as 0.1% in the diet of rabbits exerts inhibitory effect on atherogenesis, since lower levels of LDL cholesterol and higher levels of HDL cholesterol are associated with decreased cardiovascular risk.